Evidence that powerful radio jets have a profound influence on the evolution of galaxies - Rawlings, S; Jarvis, M (2004)
The relationships between supermassive black holes and the properties of their associated dark-matter halos imply that outflows from accreting black holes provide a feedback mechanism regulating galaxy formation. Accreting black holes with weak or undetectable radio jets (radio-quiet quasars) outnumber those with powerful jets (radio-loud quasars) by a factor ~10-100, so powerful-jet outflows are often neglected. However, whenever powerful jets are triggered, there is a dramatic (factor >100) step-function increase in the efficiency of feedback. We use a feedback model, together with the measured space density of flat-spectrum radio-loud quasars, to show that a powerful-jet episode probably occurred in every protocluster in the Universe. Before jet triggering, there was time for gravitational collapse to create many (~10-100) surrounding protogalaxies massive enough to host radio-quiet quasars. After triggering, the powerful jet pushes back and heats ionized gas so that it cannot fall onto these protogalaxies and cool. Once neutral/molecular gas reservoirs become exhausted, there is a synchronized shut down in both star-formation and black-hole activity throughout the protocluster. These considerations imply that radio-loud quasars have a profound influence on the evolution of all the galaxies seen in clusters today.